Analisis paket teknologi lokal dalam pengelolaan produksi madu organik untuk pasar global dan industri - Rudi Hilmanto (Jurnal Ilmu Pertanian Indonesia, 2010)
Production of honey conventionally by community do generate constraint at marketing to global market and industry. Model local technological packet is hoped improve the value sell honey commodity to go in global market and industry. Activity of production organic honey use local technological packet is hoped able to face Free Trade Agreement (FTA) for local farmer. local Technological packet at activity produce honey commodity, is expected be able to develop and strengthen production quality commodity. The objective of this research was to analyse the local technological packet at activity produce organic honey commodity to industrial and the global market in the form of technological model of management produce honey. The research method use Knowledge Base Creation constructively computer program of Agroekological Knowledge Toolkit 5 (AKT5). Result of research indicate that application local technological packet at activity produce organic honey had to watched five activity, namely: (a) system agroforestry as source of nectar and pollen; (b) to improve the stock honeybee; (c) select, breeder, making bee hive honey; (d) give meal artificial (e) time and technique of cropping, till the product was sold. The result of reseach showed that the responder group applying activity produce honey organic at species Apis cerana yield 2,5 kg each stup, rate moisture content 20°/o, not turbid, and cleared at yielded honey. Result Interpretation was showed fulfill ideal technology management target.